2021
DOI: 10.1016/j.omtm.2020.10.022
|View full text |Cite
|
Sign up to set email alerts
|

siRNA targeting Schlemm’s canal endothelial tight junctions enhances outflow facility and reduces IOP in a steroid-induced OHT rodent model

Abstract: Systemic or localized application of glucocorticoids (GCs) can lead to iatrogenic ocular hypertension, which is a leading cause of secondary open-angle glaucoma and visual impairment. Previous work has shown that dexamethasone increases zonula occludens-1 (ZO-1) protein expression in trabecular meshwork (TM) cells, and that an antisense oligonucleotide inhibitor of ZO-1 can abolish the dexamethasone-induced increase in trans-endothelial flow resistance in cultured Schlemm's canal (SC) endothelial and TM cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…This study established that AdCLU and supplementation of rhCLU decreased ECM and fibrotic process emphasizing the importance of clusterin in ECM remodeling. Concomitantly, decreasing cytoskeletal contractility, ECM, and lowering cell junction proteins including Zo‐1 can increase the outflow facility and reduce the IOP (Cassidy et al, 2021; Faralli et al, 2019; Keller et al, 2009; Pattabiraman et al, 2015b; Vranka et al, 2015). We propose that the lowering of ECM is due to a significant downregulation of profibrotic proteins including TGFβ2, PAI‐1, and TSP‐1 and significantly increasing the MMP‐2 activity (Pattabiraman et al, 2014; Pattabiraman et al, 2015b; Zhavoronkov et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This study established that AdCLU and supplementation of rhCLU decreased ECM and fibrotic process emphasizing the importance of clusterin in ECM remodeling. Concomitantly, decreasing cytoskeletal contractility, ECM, and lowering cell junction proteins including Zo‐1 can increase the outflow facility and reduce the IOP (Cassidy et al, 2021; Faralli et al, 2019; Keller et al, 2009; Pattabiraman et al, 2015b; Vranka et al, 2015). We propose that the lowering of ECM is due to a significant downregulation of profibrotic proteins including TGFβ2, PAI‐1, and TSP‐1 and significantly increasing the MMP‐2 activity (Pattabiraman et al, 2014; Pattabiraman et al, 2015b; Zhavoronkov et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Topical instillation of β2 adrenergic receptor siRNA induced a reduction in IOP of 30 ± 5% for 78–120 h in rabbits ( Loma et al., 2018 ). Besides, ZO-1 and tricellulin siRNA-targeting SC endothelial tight junctions enhancing outflow facility showed an average IOP decrease of approximately 2 mmHg in DEX-treated mice eyes after 48 h intracameral injection, representing twice that measured in normotensive controls (approximately 1 mmHg) ( Cassidy et al., 2021 ). Intracameral injection of adenovirus vector encoding wild-type human metalloproteinase 1 (AdhGRE.…”
Section: Discussionmentioning
confidence: 98%
“…Eyes, which have a clear anatomy, relative immune privilege, and relatively isolated compartment that limits systemic exposure, are a good target for RNAi therapy. RNAi-based mechanisms, especially the use of small interfering RNAs (siRNAs), have been used in research to treat several chronic diseases and have shown promising results for ocular diseases, including glaucoma ( Cassidy et al., 2021 ; Diaz-Canestro et al., 2021 ; Feng et al., 2021 ; Nguyen et al., 2012 ; Ray et al., 2017 ). Due to their high susceptibility to enzyme hydrolysis, rapid removal from circulatory system siRNA, virus vectors or nanoparticle carriers are needed.…”
Section: Introductionmentioning
confidence: 99%
“…An intracellular location of the NPs after perfusion was confirmed by TEM. Once arrived at the target cells, NPs have the great advantage to allow for an efficient cellular uptake of their therapeutic freight [ 8 ]. Macromolecular drugs in particular, such as siRNA, would otherwise be highly unstable and not be able to cross cellular membranes [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, new drugs have been approved that interfere with the fundamental pathological processes of POAG development, such as Rho-associated protein kinase inhibitors (e.g., netarsudil and ripasudil) [ 5 ] or nitric oxide donors (e.g., latanoprostene bunod) [ 6 ]. In addition to these small-molecule drugs, macromolecules, such as small interfering RNA (siRNA), are discussed as an innovative alternative to intervene disease progression [ 7 , 8 ]. However, their high molecular weight, inherent instability and strong negative charge currently prevent nucleic acids to reach a sufficiently high bioavailability in the anterior chamber of the eye [ 9 ].…”
Section: Introductionmentioning
confidence: 99%